The Effectiveness of Nigrospora sp. and Penicillium sp. As Entomopathogenic Fungi Against in Bactrocera sp. - Oktariana, Putri; Rosa, Emantis; Setiawan, Wawan Abdullah; Nurcahyani, Nuning (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2024)
Pest attacks caused by fruit flies (Bactrocera sp.) can cause damage to fruit quality. Damage can become more severe due to secondary infection by bacteria or fungi which can cause fruit to rot. This research was conducted to determine the effectiveness and morphological changes caused by the fungus Nigrospora sp. and Penicillium sp. on the mortality of Bactrocera sp. This research was conducted using a Randomized Block Design (RBD) with two factors: the type of entomopathogenic fungi and the density of spores. Entomopathogenic fungi isolates were obtained from the isolation of entomopathogenic fungi from fruit flies (Bactrocera sp.) from previous studies. The spore density used for each fungus was 105, 106, and 107 spores/mL. Each treatment unit used 5 Bactrocera sp. adults with 3 repetitions. In the isolates of Nigrospora sp. they have resulted in mortality at a spore density of 105 spores/mL of 86%, a density of 106 spores/mL of 93%, and a density of 107 spores/mL of 100%. In the isolates of Penicillium sp. all treatments resulted in 100% mortality.